Tackling rural water scarcity in South Africa: climate change, governance, and sustainability pathways - Matimolane, Selelo; Mathivha, Fhumulani I. (Frontiers in Environmental Science, 2025)
Water scarcity in rural South Africa is an escalating crisis driven by climate change, governance inefficiencies, and socio-economic disparities. This perspective synthesizes secondary data through the Integrated Water Resources Management (IWRM) and Socio-Ecological Systems (SES) frameworks, offering a novel lens that bridges macro-policy failures with micro-community resilience, unlike single-framework analyses. Drawing on existing case studies, including Cape Town’s “Day Zero” drought and the Greater Giyani Municipality, we highlight both current advances, such as smart metering, rainwater harvesting, and decentralized purification systems, and persistent vulnerabilities, including erratic rainfall, declining dam levels, and under-resourced infrastructure. The IWRM lens exposes gaps in institutional coordination, policy enforcement, and infrastructure investment that undermine equitable water distribution. The SES perspective reveals how rural communities navigate scarcity through informal networks, traditional knowledge, and local adaptation strategies, but also illustrates the limitations of these responses in the absence of state support. We argue that neither top-down governance nor grassroots innovation alone can achieve water security. Instead, sustainable solutions require hybrid, multi-scalar strategies that align regulatory reforms with community-driven resilience. Future efforts must prioritize adaptive infrastructure, context-sensitive technologies, and inclusive governance frameworks to build climate-resilient and equitable rural water systems. South Africa’s experience offers instructive lessons for global water governance, demonstrating the need for holistic, systems-based approaches that integrate technical, social, and institutional dimensions. This perspective contributes to a strategic framing for future policy and research aimed at ensuring long-term water security and sustainability in vulnerable contexts.